1998
DOI: 10.1002/(sici)1097-4547(19980815)53:4<502::aid-jnr13>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Seizure activity induces PIM-1 expression in brain

Abstract: We recently identified KID-1, a previously undescribed protein kinase induced by depolarization in PC12 cells and brain (Feldman et al., 1998). KID-1 shares a high degree of sequence homology with PIM-1, a proto-oncogene previously reported to be expressed in hematopoietic and germ cells. We examined PIM-1 expression in stimulated PC12 cells, brains of kainic acid-treated rats, and a number of tissues from untreated rats. We now report that forskolin, but not depolarization or growth factors, induces PIM-1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…However, relatively little is known about the regulation and function of Pim kinases in the CNS. Pim-1 expression has been shown to increase in the dentate gyrus of the hippocampus after systemic kainic acid administration in rats (Feldman et al, 1998) and has also been reported to be induced by plasticity-producing stimulation in the brain (Konietzko et al, 1999). The present study demonstrates that G-CSF treatment significantly increased nuclear Pim-1 expression in the injured cortex after focal cerebral ischemia.…”
Section: Discussionsupporting
confidence: 65%
“…However, relatively little is known about the regulation and function of Pim kinases in the CNS. Pim-1 expression has been shown to increase in the dentate gyrus of the hippocampus after systemic kainic acid administration in rats (Feldman et al, 1998) and has also been reported to be induced by plasticity-producing stimulation in the brain (Konietzko et al, 1999). The present study demonstrates that G-CSF treatment significantly increased nuclear Pim-1 expression in the injured cortex after focal cerebral ischemia.…”
Section: Discussionsupporting
confidence: 65%
“…STAT3 can bind directly to the Pim-1 promoter sequence and upregulate pim-1 gene expression. Reports have noted that Pim-1 is elevated after seizure (Feldman et al, 1998). We found an upregulation of Pim-1 after hypoxia-ischemia, and that this was enhanced by G-CSF treatment ( Figure 7A).…”
Section: Discussionsupporting
confidence: 63%
“…The inhibitory profiles of the three active compounds DMAT, DRB, and emodin also support other potential candidates. DMAT inhibits Dyrk1A (35), which binds and phosphorylates ␣-syn (30), and PIM-1, which is induced in the brain upon seizures and long term potentiation (59,60). DRB inhibits cyclin-dependent kinase 7 (36), which is increased in brain during aging and in Alzheimer disease (61).…”
Section: Discussionmentioning
confidence: 99%